Age and aphasia: a review of presence, type, recovery and clinical outcomes. Issue 6 (17th August 2016) - Ellis, Charles; Urban, Stephanie
Abstract : Background: Each year approximately 100, 000 stroke survivors are diagnosed with aphasia. Although stroke is associated with age, the relationship between age and aphasia is less clear. Objectives: To complete a review of the literature to examine the relationship between age and: (a) presence or likelihood of aphasia after stroke, (b) aphasia type, (c) aphasia recovery patterns, and (d) aphasia clinical outcomes. Data Sources: Articles were identified by a comprehensive search of "OneSearch, " PubMed, and individual journals: Aphasiology, Stroke and the Journal of Stroke and Cerebrovascular Diseases . Study Selection: Inclusion criteria included: age and incidence of aphasia, likelihood of aphasia, aphasia recovery, and aphasia clinical outcome. Data Extraction: Independent searches were completed by the authors. Each author independently assessed the full text of reports meeting inclusion criteria. Differences regarding study eligibility and need to proceed with data extraction were resolved by consensus. Results: 1617 articles were identified during the initial search. Forty studies including 14, 795 study participants were included in the review. The review generally demonstrated that: (a) stroke patients with aphasia are typically older than stroke with patients without aphasia and (b) aphasia type and age are associated as younger patients with aphasia are more likely to exhibit non-fluent or Broca's type of aphasia. In contrast, studies examining aphasia recovery and aphasia clinical outcomes did not demonstrate a positive relationship between age and recovery or clinical outcomes. Conclusions: Stroke is a condition of the elderly. However, age appears to only influence likelihood of aphasia and aphasia type.